Consideraciones sobre la evolución jurídica del concepto de refugiado - Sánchez Velásquez, David (Pontificia Universidad Católica del Perú, 2023)
In view of the call by the United Nations High Commissioner for Refugees (UNHCR) for Latin American States to recognize Venezuelan migrants as refugees, in accordance with the expanded definition contained in the Cartagena Declaration on Refugees (1984), it is necessary to review the evolution of the refugee concept and to take a closer look at the regulations that the most important regional systems for the protection of human rights have adopted on this legal concept. In this way, we will better understand the reasons that allow us to affirm that Venezuelan migrants should be recognized as refugees.

A propósito de la invocación del Alto Comisionado de las Naciones Unidas para los Refugiados (ACNUR) para que los Estados latinoamericanos reconozcan a los migrantes venezolanos como refugiados, en atención a la definición ampliada que contempla la Declaración de Cartagena sobre Refugiados (1984), resulta necesario repasar la evolución del concepto de refugiado y tomar ligero contacto con la regulación que los más importantes sistemas regionales de protección de los derechos humanos han adoptado sobre esta figura jurídica. De esa manera, comprenderemos de mejor manera las razones que nos permiten afirmar que los migrantes venezolanos deben ser reconocidos como refugiados.
Considerations on the legal evolution of the refugee concept
Keywords: International Refugee Law; Convention Relating to the Status of Refugees (1951); OAU Convention on Refugees (1969); Cartagena Declaration on Refugees (1984); Derecho Internacional de los Refugiados; Convención sobre el Estatuto de los Refugiados (1951); Convención de la OUA sobre refugiados (1969); Declaración de Cartagena sobre Refugiados (1984); https://purl.org/pe-repo/ocde/ford#5.09.01